Antinomicity and the axiom of choice. A chapter in antinomic mathematics - Asenjo, Florencio G. (Logic and Logical Philosophy, 2003)
The present work is an attempt to break ground in mathematics proper, armed with the accepting view just described. Specifically, we shall examine various versions of antinomic set theory, in particular the axiom of choice, keeping the presentation as intuitive as possible, more in the manner of a nineteenth century paper than as a thoroughly formalized system. The reason for such a presentation is the conviction that at this point it should be the mathematics that eventually determines the logic, rather than the other way around.